Reprint of ‘The Myth of a Normal Muslim: ‘Aql, Taklīf, and New Islamic Approaches to Neurodivergence’ - Choudhury , Naba Ul-Alam (University of Darussalam Gontor Press, 2025)
This paper explores the intersection of Islamic concepts, such as ‘aql (intellect) and taklīf (legal responsibility), with the experiences of neurodivergent individuals, particularly those with autism. It argues for a re-evaluation of traditional Islamic understandings of disability to incorporate modern perspectives on neurodiversity. The research highlights that high-functioning autistic individuals possess the capacity to engage with religious obligations and that Islamic practices can be adapted to accommodate their unique needs. By advocating for an inclusive approach, the paper calls for a dialogue between classical Islamic jurisprudence and contemporary insights into neurodiversity, aiming to foster a supportive environment for neurodivergent Muslims within their communities. Ultimately, it seeks to provide a framework for understanding neurodiversity through an Islamic lens, promoting both spiritual engagement and social inclusion.Editorial Notes:A publisher’s error resulted in this article appearing in the wrong issue. The article is reprinted here for the reader’s convenience and for the continuity of this issue. This article is a reprint of a previously published article. For citation purposes, please use the original publication details; Choudhury , N. U.-A. (2024). P. 43-67